Analysis of thermal chromaticity stability, energy transfer and colour tunablity of Dy3+-Eu3+ doped BBZL glasses for high-power W-LED applications. Issue 3 (1st February 2023) - Xu, Shiyu; Fu, Junjie; Liu, Xuening; Yuan, Meiyu; Zhang, Chaoqun; Wang, Haibo; Liu, Guangxi; Cui, Sheng
Abstract: A family of highly thermal chromatic stable Dy 3+ -Eu 3+ doped B2 O3 -Bi2 O3 -ZnO-Li2 O (BBZL) glass samples was synthesised using the high-temperature melt quenching technique. The optical and thermal stability properties of the samples were analysed using their fluorescence spectra at various temperatures, fluorescence lifetime decay times and colour coordinates. The Dy 3+ -doped BBZL (BBZL: Dy) glass samples generated cold white light when exposed to ultraviolet (UV) light, while the Dy 3+ -Eu 3+ -doped BBZL (BBZL: DyEu) glass samples emitted neutral and warm white light, which can be attributed to the introduction of Eu 3+ that substantially enhanced the colour rendering of samples. An overlap of the excitation-emission spectra of Eu 3+ and Dy 3+ indicated an energy transfer between Dy 3+ and Eu 3+ . Under a 350 nm excitation, the fluorescence lifetime of BBZL: DyEu decreased from 0.5348 to 0.3642 ms. Using the Dexter theory, the energy transfer between Dy 3+ and Eu 3+ was demonstrated to be an electric dipole-electric dipole leap. The chromaticity shifts of BBZL: DyEu were 8.60 × 10 −4 and 9.40 × 10 −4 at 448 and 498 K, respectively, reflecting the high thermal stability of the sample chromaticity. The study demonstrated that Dy 3+ -Eu 3+ doped borate glasses can be used as tunable luminescent materials in high-power white light-emitting diodes to mitigate the chromaticity shift in fluorescent materials at high temperatures.